Green energy-sourced AI-controlled multilevel UPQC parameter selection using football game optimization - Srilakshmi, Koganti; Rao, Gummadi Srinivasa; Balachandran, Praveen Kumar; Senjyu, Tomonobu (Frontiers in Energy Research, 2024)
The power quality (PQ) has been significantly affected by the integration of intermittent non-conventional sources (NCS) into the local distribution system in addition to the adoption of power electronic technologies to regulate nonlinear loads. This article combines the H-bridge cascade 5L-UPQC with wind power generation system (WPGS), solar photovoltaic power generation system (SPVGS), and battery storage system (BSS) as an effective approach to address PQ problems. The utilization of the levenberg-marquardt back propagation (LMBP) trained (artificial neural network) ANNC in the UPQC is recommended for generating appropriate reference signals for the converters. This eliminates the requirement for conventional complex conversions such as abc, dq0, and αβ. Besides, artificial neuro fuzzy interface system (ANFIS) is recommended for achieving DC link balancing. The foot ball game optimization (FBGO) is utilized to determine the optimal shunt and series filter characteristics. The major objectives of the proposed system are to reduce current waveform irregularities, resulting in a decrease in total harmonic distortion (THD), an enhancement in power factor (PF), the mitigation of supply voltage imbalances and disturbances, and the maintenance of a steady distributed load control voltage (DLCV) despite variations in load, solar irradiation, and wind velocity. The efficiency of the suggested strategy is assessed using four case studies that involve different loads, variable wind velocities, and source voltage balancing conditions. Based on the simulation studies and obtained results, the suggested method significantly decreases the THD to values of 2.91%, 3.63%, 3.75%, and 3.50%. Additionally, it achieves a power factor of unity, which is considerably lower compared to other multilevel schemes that use the traditional Symmetrical Reference Frame (SRF) and (Instantaneous reactive power) pq methods. The design has been executed using the MATLAB/Simulink program.